KONSEP DIRI ANGGOTA DEWAN PERWAKILAN DAERAH REPUBLIK INDONESIA (DPD – RI) PADA KONTEKS KOMUNIKASI ANTARBUDAYA - Teuku Yuliansyah (Linimasa : Jurnal Ilmu Komunikasi, 2022)
Indonesia is multicultural, which means that it does not only recognize the plurality of certain ethnic groups or cultures, but also emphasizes equality between these cultures. The existence of ethnicity should be considered as the nation's essential wealth that can be used to form social relations, to enrich the nation's cultural assets. In this case, multiculturalism accommodates two (2) things that are contradicted, namely 'Difference' and 'Equality'. Thus, despite the high level of heterogeneity, "vertical and horizontal conflicts", can be reduced because each culture is given the freedom to show its identity and carry out life more autonomously while getting equal recognition of the existence and uniqueness of each. This is the reason why this research was conducted at State Institutions such as DPD – RI.The purpose and objective of this research is to explore opinions and get a general idea of ​​how the strategy of DPD – RI Members to construct their self - concept based on their region of origin in the context of intercultural communication.This study uses a qualitative method with a constructivist paradigm that focuses on Alfred Schutz's tradition of social phenomenology, which is associated with the concept of symbolic interaction.The results showed that there were three (3) self - concept models of the informants, namely: the conservative model; adaptive; interactive, based on three (3) classification, namely: motive – adaptation – interaction.The conclusion obtained is that the scope of the informant's self-concept is not limited to social and political communication, but is closely related to intercultural communication. The slogan “Bhinneka Tunggal Ika” has become a symbol of intercultural communication for DPD – RI members as the end result of how they interpret their self - concept.